Teaching Social Justice in an Information Literacy Course: An Action Research Case Study - Rioux, Kevin (Qualitative and Quantitative Methods in Libraries; 2014: Special Issue: Social Justice, Social Inclusion, 2017)
This paper presents a brief action research case study of a graduate-level information literacy course. Approaches used to teach social justice concepts in this course and evidence of achieving both information literacy and social justice outcome goals are examined and described.  Results suggest that social justice course orientations enhance and expand information literacy outcomes.